Vermicompost as a substrate in the production of peppermint (Mentha piperita L.) - Romero Figueroa José Cruz; Rodríguez Mendoza Ma. de las Nieves; Gutiérrez Castorena Ma. del Carmen; Sánchez Escudero Julio (Revista Mexicana de Ciencias Agrícolas, 2018)
The objective was to compare the carbon nitrogen vermicompost as substrate in the production and nutrient concentration of peppermint (Mentha piperita L.). There were three initial relationships compost C/N 45, 35 and 26, for these two organic matters were used; maize straw (PM) and cow manure (EB).At the end of the vermicomposting process we harvested vermicompost (VC) and obtained C/N ratios of 21, 27 and 13 respectively. For the nutritional evaluation of vermicompost we designed a factorial experiment (3 x 2) with three C/N ratios, with and without the addition of organic effluents (derived from vermicomposting process) in a completely randomized design with 10 replications. Peppermint seedlings were placed in pots containing a mixture of vermicompost: perlite (3:1, v: v). 73 days after transplanting (DAT) nitrates were determined (NO-3) and potassium (K +) with mobile Ionomers Horiba®, then the plants were harvested and quantified the fresh and dry weight of leaves, stems and roots, dry matter rates and the proportion of shoots and roots. Plants grown in the VC 13 had the highest concentration of NO-3 (12 750 ppm), and K+ (10, 100 ppm) also favoring the development of the crop which is ref lected in Total Biomass (16.97 g) compared to the plants grown in VC 21 and 27. Vermicompost with initial C/N 26 produces a material which can be used as substrate for the cultivation of fresh consumption mint or dry.